2018
DOI: 10.1007/s00125-018-4573-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomic profile of incident diabetes

Abstract: Branched chain amino acids may play a role in diabetes development. Our study is the first to report asparagine as a protective biomarker of diabetes risk. The serum metabolome reflects known and novel metabolic disturbances that improve prediction of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 38 publications
6
82
0
1
Order By: Relevance
“…Two prospective observational studies in the United States found that baseline plasma asparagine was a protective marker of diabetes (28,29). In these researches, ndings about aspartate were accordant with ours, but results about asparagine were opposite to ours.…”
Section: Discussionsupporting
confidence: 49%
“…Two prospective observational studies in the United States found that baseline plasma asparagine was a protective marker of diabetes (28,29). In these researches, ndings about aspartate were accordant with ours, but results about asparagine were opposite to ours.…”
Section: Discussionsupporting
confidence: 49%
“…However, in humans the benefit of BCAA supplementation is less evident 23 , 24 . A possible reason might be that not only low levels of BCAAs associate with adverse health outcomes: In contrast to AD and mortality, higher levels of valine and further BCAA have been linked to prevalent and incident type 2 diabetes (T2D) 25 , 26 and incident CVD in women 27 . Thus, balancing the potential positive effects of BCAA supplementation with potential adverse effects 28 might be crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on metabolomics in T2D highlights the important role of amino acid profiling, particularly branched-chain amino acids (BCAA) for diabetes risk assessment [15][16][17] . Several other metabolites have been reported as significantly associated with diabetes prevalence; these include reduced levels of glycine, lysophosphatidylcholine (LPC) (18:2) as well as increased levels of acetylcarnitine 18 .…”
mentioning
confidence: 99%